Height and Diameter Measurement of Eucalyptus Urophylla in Batur Mountain Nature Tourist Forest, Indonesia - I Gusti Ayu Diah Yuniti; Jhon Hardy Purba; Liris Lis Komara; Nanang Sasmita (Green Engineering Society, 2022)
Batur Forest is a volcanic area that was an ex-volcanic eruption. Efforts to rehabilitate forests with critical land were by planting Eucalyptus urophylla. The aim of the study was to examine the adaptation of Eucalyptus urophylla species in critical areas of former volcanic eruptions that were dominated by hard rocks. The research was done for a year (2019-2020). The method used was a species test with a permanent block plot design from 4 age levels, 1 year, 5 years, 10 years, and 15 years. The study results showed growth of 1.02 cm in diameter and 1.10 m in height (1 year), 6.50 cm in diameter and 11.00 m in height (5 years), 13.25 cm in diameter and 18.40 m in height (10 years), and a diameter of 20.48 cm and a height of 23.00 m (15 years). Eucalyptus urophylla experienced the best tree diameter growth after 10 years old and on the contrary experienced a decrease in height. The Eucalyptus urophylla level of adaptation and suitability of volcanic soils with low fertility and rocky soil is a recommendation to increase the quantity of this species of planting. So that the forest succession from rocky thickets to tree vegetation is faster than natural processes. Eucalyptus urophylla species is one of the flora that makes up the savanna forest ecosystem and volcanic critical land in eastern Indonesia.